The Community Education Model: Learning Opportunities for Rural Adults - Dawn Ramsey (Educational Considerations, 1986)
Community education programs are highly effective in generating community spirit, in mobilizing scarce resources, and in encouraging learning as a lifelong vocation. For rural areas, community education serves a vital role in linking communities with resources and individuals with broader educational resources.